Application of serum STIM1, AOPPS, and urinary NGAL, AGT in the diagnosis of hypertensive nephropathy - Baohua Li; Chunsheng Wang; Deng Ouyang; Haofeng Xu; Zhile Wu; Xin Yang (Renal Failure)
Objective We aim to explore the diagnostic value of early detection of serum stromal interaction molecule 1 (STIM1), advanced oxidation protein products (AOPPs), urinary neutrophil gelatinase-associated lipocalin (NGAL), and angiotensinogen (AGT) in hypertensive nephropathy (HN).Methods A retrospective study was conducted on 123 patients with primary hypertension. Based on the diagnostic criteria for HN, patients were divided into the HN group (n = 58) and simple hypertension group (n = 65). Additionally, 60 healthy individuals undergoing routine physical examinations were selected as the control group. The concentrations of serum STIM1, AOPPs, and urinary NGAL and AGT were assessed.Results The HN group exhibited higher levels of serum STIM1, AOPPs, and urinary NGAL and AGT than the simple hypertension and control groups. Pearson correlation analysis revealed that serum STIM1 and AOPPs were positively correlated with BUN, UN, and SCr and negatively correlated with eGFR; urinary NGAL and AGT were positively correlated with blood urea nitrogen, uric acid, and serum creatinine and negatively correlated with eGFR (all p < 0.05). Logistic regression analysis displayed a correlation between HN and serum STIM1 (OR: 1.019; 95%CI: 1.049-1.148), AOPPs (OR: 1.312; 95%CI: 1.129-1.526), and AGT (OR: 1.436; 95%CI: 1.183-1.742) (p < 0.05). ROC curve analysis demonstrated that the combined detection of serum STIM1, AOPPs, and urinary NGAL, AGT had a higher AUC for predicting HN compared to individual tests.Conclusion Detection of serum STIM1, AOPPs, and urinary NGAL and AGT has diagnostic value in HN, providing a reference for early diagnosis and timely treatment of HN.